Hereditary aspects of median-ulnar nerve communications. Issue 1 (January 1980) - Crutchfield, C A; Gutmann, L
Abstract : Median-ulnar nerve communications, resulting in anomalous innervation of intrinsic hand muscles, was found to occur in 28% of the general population and 62% of family members of five propositi with this variant. This variant appears to be dominantly inherited.